2016
DOI: 10.1002/psb.1496
|View full text |Cite
|
Sign up to set email alerts
|

The hidden problem of herb‐drug interactions

Abstract: Potentially harmful interactions between herbs and prescription medicines are common, yet healthcare professionals often do not ask about herbal remedies when prescribing and patients do not volunteer that they are taking them. This article discusses the types of herb‐drug interaction that can occur and how they can be recognised and avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…L. cardiaca also potentiates antithrombotic and antiplatelet effects, increasing the risk of bleeding. When administered concomitant with benzodiazepines, motherwort can also have a synergistic sedative effect resulting in coma [73].…”
Section: Dosage and Toxicologymentioning
confidence: 99%
“…L. cardiaca also potentiates antithrombotic and antiplatelet effects, increasing the risk of bleeding. When administered concomitant with benzodiazepines, motherwort can also have a synergistic sedative effect resulting in coma [73].…”
Section: Dosage and Toxicologymentioning
confidence: 99%
“…Based on Yellow Card reports, the MHRA warned that patients taking warfarin should limit or avoid drinking cranberry juice and that St John's wort could reduce the efficacy of concurrent hormonal contraceptives medicines and implants. 3 Although the Yellow Card Scheme began with ADRs, the system now encompasses adverse incidents related to medical devices, including concerns about the performance of diagnostic assays and technologies. The Yellow Card Scheme also includes counterfeit and defective medicines (those that are not of an acceptable quality), and from May 2016, safety concerns associated with e-cigarettes.…”
Section: The Yellow Card Schemementioning
confidence: 99%
“…Modern system of medicine has emerged as the primary choice for the treatment of nearly all types of health-related issues, although, it is mainly based on the nonholistic/bug killing/target-based approach, which ultimately leads to future side effects (notable in case of chronic disorders such as cancer, diabetes, arthritis, etc). 1–3 However, patients with such chronic illnesses directly/indirectly undergo combinational/multimodal therapy with or without the knowledge of physicians, leading to potential herb–drug interactions (HDIs). 1 The MD Anderson Cancer Centre, in USA, reported that 52% of their cancer patients had used at least one form of complementary and alternative medicine (CAM), and 77% of those were using herbs.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 However, patients with such chronic illnesses directly/indirectly undergo combinational/multimodal therapy with or without the knowledge of physicians, leading to potential herb–drug interactions (HDIs). 1 The MD Anderson Cancer Centre, in USA, reported that 52% of their cancer patients had used at least one form of complementary and alternative medicine (CAM), and 77% of those were using herbs. 4 While, according to the World Health Organization (WHO) and other reviews >80% world's population uses CAM for their health care needs and particularly in western countries CAM has become increasingly popular over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation